Uropatia obstrutiva alta. - L C Pinheiro; A M Ferreira (Acta Médica Portuguesa, 1999)
Upper urinary tract obstruction is very frequent. The authors present a review of the etiology and pathogenesis of upper urinary tract obstruction. The clinical aspects and diagnosis are described in detail and the most appropriate complementary exams are pointed out. Finally, the authors discuss the therapeutic options available and the prognosis.